Background to the Western Isles project (Scottish Historical and Archaeological Internet Reports, 2003)
This chapter presents the background to the project, details of the coring programme and the technique of tapestry excavation (excavation of a strip of deposits along an exposed face), excavation methodology, data management, methods for observation and interpretation and presentation of results.